Custos intangíveis nos relatórios de administração das empresas brasileiras no período de 2007 a 2009 - Boff, Caroline Dal Sotto (Universidade do Vale do Rio dos Sinos, 2011)
This study aimed to recognize the intangible costs related to intangible factors existing in the reports of directors of companies in the traditional segment of the Bovespa during the years 2007 to 2009. The theoretical framework was based on market value offirms in intangible factors (positive and negative), these resources are intangible assets and liabilities and, finally, the intangible costs. Through the reports of directors of companies listed on Bovespa traditional segment, we used the program Wordstat to see which were the most frequently cited of which used only the 500 / 1. Among the most cited are from those Who had ties tointangibles. These associations were made resulting in six intangibles. Identified the three most cited in each sector of the Bovespa and the intangible costs associated with them. It was concluded that the evidence found in the reports of directors relating to intangible costs vary across sectors, since these factors were also distinguished by priority sector. However, the costshighlighted by each factor were very similar or the same source. It can be observed that among the companies surveyed, not allreports submitted in his administration enough information for an analysis of factors and intangible costs.
Keywords: Management reports; Intangibles; Intangible costs; Relatórios de administração; Fatores intangíveis; Custos intangíveis; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis